ANALISIS KELAYAKAN FINANSIAL USAHA AGROINDUSTRI PAKAN IKAN DI KECAMATAN KUOK KABUPATEN KAMPAR (Studi Kasus Usaha Pakan Ikan Bapak Sulaiman) - Fitri, Laila; Edwina, Susy; ', Yusmini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to analize the financial feasibility and to analize the level of sensivity of fish feed agroindustry business. This research uses the case study method, the object of the research is a fish feed business in Kuok district Kampar regency. Investment criteria used in analyzing the financial feasibility is Net Present Value (NPV), Internal Rate of Return (IRR) dan Net Benefit Cost Ratio (Net B/C). The results of the research showed that fish feed agroindustry business is feasible to run and developed with the value of NPV as Rp. 1.727.012.550 (NPV bigger than zero), Net B/C of 3,08 (Net B/C bigger than one) and IRR stay at DF 55,34% (IRR bigger than DF 12%). The results of the sensitivity analysis showed that if the business have a risk from the increases bran prices by 14%, dried fish price increases of 8%, a decrease in fish feed production 25% and decline of production time to 17 days in 1 month, then business is not sensitive to the risks and the business is worth tobe continued. Resulting risk is not worth the effort, in case sensitivity the increases bran prices by 16,15%, dried fish price increases of 26,96%, increases bran princes and dried fish simultaneously 11%, a decrease in fish feed production  52,46% and decline of production time to 11 days in 1 month. Keywords: Fish Feed Agroindustry, Financial Feasibility, Sensivity